The Impact of Communication Ethics on The Communication Quality in Interpersonal Relationships - Medika Oga Laksana; Nurhaliza Nurhaliza (Eduvest - Journal of Universal Studies, 2023)
Communication ethics are very important in establishing interpersonal relationships. In every communication, ethics are crucial in maintaining the quality of communication and establishing good relationships between individuals. However, there are often still disagreements and misunderstandings in interpersonal communication, which results in poor communication quality. Therefore, research on the impact of communication ethics on the quality of communication in interpersonal relationships is very important to do. This research aims to identify the impact of communication ethics on the quality of communication in interpersonal relationships. This research uses a qualitative approach with a case study type. This research was conducted by means of in-depth interviews to a number of respondents who were taken by purposive sampling technique. Observation techniques were also used to observe respondents' behavior in interpersonal communication situations. The data were analyzed descriptively using a qualitative approach. The results showed that communication ethics play an important role in improving the quality of communication in interpersonal relationships. Good communication ethics can create a conducive atmosphere in communication, build trust and reduce disagreements in interpersonal communication. Conversely, poor communication ethics can hinder the quality of communication and worsen interpersonal relationships. Therefore, it is important for individuals to understand and apply good communication ethics in every interpersonal communication situation.